Awareness of Healthy Life and Mental Health of Nursing College Students Before and After the COVID-19 Outbreak with the Involvement in Sports Activities - Chungyun Kim, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study analysed the awareness of healthy life and mental health among college nursing students, both before and after the COVID-19 outbreak. Additionally, their participation in sports was examined. This study aimed to compare two types of results based on the analysis conducted. A total of 982 individuals took part in a survey examining the awareness of healthy living, mental health, and interest in sports activities among nursing college students in Korea. This included 492 students surveyed before the COVID-19 outbreak and 490 individuals surveyed after the outbreak. The study's findings were as follows: First, there were notable disparities in awareness of a healthy lifestyle pre- and post-the COVID-19 pandemic. This includes the importance placed on leading a healthy life, the level of interest in maintaining one's health, the perceived usefulness of health-related information, an overall understanding of what constitutes a healthy lifestyle, and engagement in sports activities. Furthermore, notable variations were observed in the sub-factors of mental health, namely emotional health, social health, psychological health, and overall mental health. Second, the level of awareness regarding a healthy lifestyle varied significantly across different grade levels prior to the COVID-19 outbreak. Notably, the upper grades (3rd and 4th graders) exhibited a significantly higher level of awareness compared to the 1st and 2nd graders. The level of mental health varied significantly across different grade levels, with higher grades showing a higher degree of mental well-being. This correlation can be attributed to increased participation in sports. Third, there were no notable variations in the awareness of healthy living and mental health following the COVID-19 outbreak across different grade levels. The research findings will provide valuable data to support the development of nursing college students into professional nurses. This data will enhance their understanding of healthy living and mental well-being, as well as encourage their participation in sports.